Climate-Related Disclosure and Financial Performance: Which One is Affected by CEO Narcissism? - Putikadea, Insyirah; Kusumaningsih, Ambar (Journal of Economic, Management, Accounting and Technology (JEMATech), 2025)
The financial sector has an essential role in the economy and acts as a catalyst in the transition toward economic sustainability. Consequently, the Financial Services Authority (OJK) periodically requires the banking sector to consistently report its financial performance through Financial Reports and its non-financial performance in Sustainability Reports. In this context, the CEO plays a pivotal role in strategic decision-making related to corporate performance, including financial reporting and sustainability disclosure. CEO narcissism is considered an individual psychological characteristic that significantly impacts organizational functions and corporate strategic decisions. This study investigates the impact of CEO narcissism on Climate-Related Disclosure and Financial Performance. Using a sample of 144 observations of banking and financing companies on the Indonesia Stock Exchange (IDX) for 2016–2022. This study uses the Fixed Effect Model as regression estimation model. The results show that CEO narcissism positively affects Climate-Related Disclosure whereas CEO narcissism has no effect on Financial Performance. The upper echelons theory states that CEO psychological characteristics impact organisational functions. This theory supports the relationship between CEO Narcissism and Climate-Related Disclosure that narcissistic CEOs tend to get a good reputation in the public as a leader who is responsive to environmental issues so they encourage the company to provide information related to GHG as a form of corporate responsibility, while in the financial performance, narcissistic CEO decisions are like double-edged sword that might lead either performance increasing or decreasig so the role of Corporate Governance is needed to control CEO decisions which bring beneficial to the company.